High strain and low social support at work as risk factors for being the target of third-party workplace violence among healthcare sector workers: Job stress factors and third party violence - Balducci, Cristian; Vignoli, Michela; Dalla Rosa, Gloria; Consiglio, Chiara (La Medicina del Lavoro, 2020)
Introduction: Healthcare workers are particularly vulnerable to third-party workplace violence. The experience of work-related stress, by threatening the psychological balance of healthcare workers, making them less effective in managing the relationship with patients and their family members, may significantly contribute to third-party violence. Objective: To investigate whether stress-related psychosocial situations at work as defined by the widely known Demand-Control model, and the level of work-related social support, act as risk factors for third-party violence among healthcare workers. Specifically, we explored whether the risk of violence is higher in situations associated with higher levels of work-related stress (i.e., active or passive situations, and especially the high strain situation) when compared to a work situation related to lower levels of stress (i.e., low strain situation). We also explored whether the risk of violence is lower at higher levels of social support. Method: Cross-sectional study on 633 healthcare workers. Psychosocial work situations and third-party workplace violence have been operationalized by using well validated scales. Results: Logistic regressions including a number of relevant covariates (e.g., gender, job role, night shift work) revealed that, compared to a low strain situation, an active or passive situation had an increased risk for workplace violence. However, the highest risk was observed for a high strain situation (i.e., the situation associated with the highest level of work-related stress). High social support acted as a protective factor. Conclusion: Healthcare workers’ experience of stress at work may make them more vulnerable to third-party violence. Ensuring better psychosocial working conditions may contribute to the prevention of workplace violence and its consequences.